1998
DOI: 10.1111/1469-7610.00310
|View full text |Cite
|
Sign up to set email alerts
|

The Parenting and Family Functioning of Children with Hyperactivity

Abstract: This study examined the parenting and family life correlates of childhood hyperactivity in a community sample of London school children. Twenty-eight boys with pervasive hyperactivity were compared to 30 classroom control children on a range of parenting and family functioning measures. Results showed that poor parent coping and the use of aggressive discipline methods were significantly associated with hyperactivity after adjusting for the effects of conduct disorder and parent mental health. The best parenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0
18

Year Published

2002
2002
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 51 publications
4
45
0
18
Order By: Relevance
“…Results with regard to hostile parenting and parental warmth and consistency are consistent with previous research, which has found parents of children with ADHD to use less positive and more aggressive parenting behaviours (such as parents losing their temper and using physical punishment more frequently) [32,46]. The consistent parenting and inductive reasoning measures used in this study, which are also used by the LSAC [49], investigate more specific aspects of parenting to many previous studies, which have focussed more on general 'positive' and 'negative' parenting behaviours and parental aggression and punishment [23,27,32,46].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Results with regard to hostile parenting and parental warmth and consistency are consistent with previous research, which has found parents of children with ADHD to use less positive and more aggressive parenting behaviours (such as parents losing their temper and using physical punishment more frequently) [32,46]. The consistent parenting and inductive reasoning measures used in this study, which are also used by the LSAC [49], investigate more specific aspects of parenting to many previous studies, which have focussed more on general 'positive' and 'negative' parenting behaviours and parental aggression and punishment [23,27,32,46].…”
Section: Discussionsupporting
confidence: 89%
“…The consistent parenting and inductive reasoning measures used in this study, which are also used by the LSAC [49], investigate more specific aspects of parenting to many previous studies, which have focussed more on general 'positive' and 'negative' parenting behaviours and parental aggression and punishment [23,27,32,46]. Our results provide more specific information regarding the parenting styles in young school-aged children with symptoms of ADHD.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations